diff --git a/vignettes/Equations.Rmd b/vignettes/Equations.Rmd new file mode 100644 index 0000000..c1fdc7f --- /dev/null +++ b/vignettes/Equations.Rmd @@ -0,0 +1,92 @@ +--- +title: "Equations" +output: + bookdown::html_document2: + number_sections: no + bookdown::pdf_book: + number_sections: false + toc: false + latex_engine: xelatex + extra_dependencies: + amsmath: null +vignette: > + %\VignetteIndexEntry{Equations} + %\VignetteEngine{knitr::rmarkdown} + %\VignetteEncoding{UTF-8} +--- + +```{r, include = FALSE,echo=F} +knitr::opts_chunk$set( + collapse = TRUE, + comment = "#>" +) +``` + +```{r setup, echo =F,message=F} +library(arfit) +``` + + +\begin{equation} + Y_t = \beta_0 + \beta_1 t + \epsilon_t (\#eq:one) +\end{equation} + +--- + +\begin{equation} + +\mathrm{L}\left( \underline{\theta}; \underline{y} \right )= \prod^n_{t=2} p\left(Y_t = y_t | Y_{t-1}=y_{t-1}\right) p\left(Y_1=y_1 \right) (\#eq:two) +\end{equation} + +--- + +\begin{align} +logL\left( \underline{\theta}; \underline{y} \right ) = & -\frac{n}{2}log2\pi - nlog\sigma + \frac{1}{2}log(1-\phi^2) \notag \\ +& -\frac{1}{2\sigma^2}\left( (1-\phi^2)(y_1-\beta_0-\beta_1)^2 + \sum^n_{t=2}(y_t - \phi y_{t-1}-\beta_0(1-\phi^2) -t\beta_1 + \phi(t-1)\beta_1)^2 \right) (\#eq:three) +\end{align} + +--- + +\begin{equation} +\hat\sigma^2 = \frac{1}{n}\left( (1-\phi^2)(y_1-\beta_0-\beta_1)^2 + \sum^n_{t=2}(y_t - \phi y_{t-1}-\beta_0(1-\phi^2) - t\beta_1 + \phi(t-1)\beta_1)^2 \right) (\#eq:four) +\end{equation} + +--- + +\begin{align} +logL\left( \underline{\beta}, \phi; \underline{y} \right ) &= const. + \frac{1}{2}log(1-\phi^2) \notag \\ +&-\frac{n}{2}log\left( (1-\phi^2)(y_1-\beta_0-\beta_1)^2 + \sum^n_{t=2}(y_t - \phi y_{t-1}-\beta_0(1-\phi^2)-t\beta_1 + \phi(t-1)\beta_1)^2 \right) \\ + +&= const. + \frac{1}{2}log(1-\phi^2) \notag \\ +&-\frac{n}{2}log\left( (1-\phi^2)(y_1-X_1\underline{\beta})^2 + \sum^n_{t=2}(y_t - \phi y_{t-1}-X_t\underline{\beta} + \phi X_{t-1}\underline{\beta})^2 \right) (\#eq:five) +\end{align} + +--- + +\begin{align} +logL\left( \underline{\beta}, \underline{\phi},\sigma; \underline{y} \right ) &= -\frac{n}{2}log(2\pi) -\frac{n}{2}log(\sigma^2) +\frac{1}{2}log \left|V_p^{-1} \right| +\\ +&-\frac{1 }{2 \sigma^2} (\underline{y_p}-\underline{\mu_p})^T V_p^{-1}(\underline{y_p}-\underline{\mu_p}) \\ + +&- \frac{1}{2\sigma^2}\sum^n_{t=p+1} (y_t - c - \phi_1y_{t-1} - ... - \phi_p y_{t-p})^2 \\ (\#eq:six) + +\end{align} + + +where + +$\left|V_p^{-1} \right|$ is determinant of inverted matrix $V_p$, + +$\sigma^2V_p$ = variance-covariance matrix of order p, + +$\underline{\mu_p} = X_p\underline{\beta}$, and + +$X_p$ is the $p_{th}$ row of the design matrix corresponding to time t = p + +$c$ = function of fitted terms $X_t\underline{\beta}$ + + + + + +